EXCELLENT SERVICE: THE ROLE OF LEARNING MANAGEMENT SYSTEM IN IMPROVING THE QUALITY OF EDUCATION IN MADRASAH - Rusdiah, Nadira; Sholiha, Santri Asiatus (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to examine the application of the "Service Excellent" concept through the utilization of the Quipper School platform to enhance the quality of education at Madrasah Aliyah Nurul Jadid. The study is grounded in the effectiveness of the Quipper School platform as a strategy for improving education quality in Madrasah Aliyah Nurul Jadid. The primary focus of the research is on engaging learning experiences through a Learning Management System (LMS), with the findings indicating a positive contribution to the quality of education. To uncover these aspects, the researcher employed a qualitative approach with a case study design. The data collection process involved observation, in-depth interviews, and documentation. Miles and Huberman's data analysis technique, comprising data reduction, data display, and verification, was applied. The research reveals that the implementation of the "Service Excellent" concept through the Quipper School platform at Madrasah Aliyah Nurul Jadid has successfully improved the quality of education, particularly in three aspects: 1) Engaging and innovative learning, 2) Collaboration and communication, 3) Monitoring and evaluating student progress.